Factors which influence the decision of sexual offenders against children to attend a sex offender treatment programme at Te Piriti or Kia Marama : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Norrie, Joan (Massey University, 1998)
Treatment of individuals who sexually offend against children has been shown to be associated with reductions in recidivism both in New Zealand, (Johnston, 1996) and overseas (Gendreau, 1996). Laven (1993) and Jury (1993) found in two New Zealand studies of incarcerated child sex offenders that when they were offered treatment to help them address their offending they more often than not declined. Barbaree (1991) noted that offenders often present as denying, minimising, rationalising or being vague about their sexual offending behaviours. Treatment for incarcerated individuals who have sexually offended against children is provided by the New Zealand Department of Corrections Psychological Service specialist prison-based Child Sex Offender Treatment Programme at Auckland (Te Piriti) and Christchurch (Kia Marama). However, participation in the programme is voluntary. The main purpose of the study was to examine the effects of a motivational and educational pretherapy intervention, First Step, on factors such as Stage of Change and Victim Empathy which were believed to be associated with the decision to seek entry to the Sex Offender Treatment Programme. A secondary purpose was to investigate which factors the child sex offenders considered while making their decision to seek or decline treatment in the programme. The subjects were 104 male incarcerated offenders convicted of sexual offences against children under the age of sixteen years. They were resident in one of three minimum security prisons, Tongariro/Rangipo, Ohura and Waikeria, New Zealand. All of the subjects were referred by the prison Case Management Committee to Department of Corrections, Psychological Service for assessment when they arrived in the prison. Of the total of 104 participants, 39 attended First Step. The other 65 were involved in a related study (Knowles, 1997) at Waikeria Prison. They were included to provide additional information on select issues related to helpseeking. Participation was voluntary and access to the First Step programme was not contingent on participation in the study. Also, there were no custodial consequences (e. g., temporary paroles or early release) contingent on participation in the study. The design for the treatment portion of the study was a two by two factorial, repeated measures design with two conditions, a wait-list control and a treatment condition (First Step). An assessment of treatment readiness and victim-specific empathy was made using the University of Rhode Island Change Assessment (URICA) questionnaire based on Prochaska, DiClemente et al's (1982, 1985, 1989, 1991, 1995) Transtheoretical Stages of Change model and Marshall et al's (1995) Person Specific Empathy Scale which were administered at pre and post wait-list and treatment conditions. The results of this study provide important data for enhancing our understanding of the effects of a pre therapy intervention on motivation and of the factors that influence the incarcerated child sex offender's decision to seek entry to a Sex Offender Treatment Programme. There was evidence that the motivational and educational intervention, the First Step programme, had an influence on the way that the offenders thought about their offending behaviour. In particular, this was supported by a general pattern of movement through the Stages of Change as illustrated by changes in the numbers of offenders in identified Stages of Change clusters. The support for First Step further buttresses Barbaree (1991) and O'Donohue and LeTourneau (1993) proposals for the necessity, particularly in cases where the problem is denied, for a pre-treatment intervention designed to encourage a frame of mind that is more amenable to treatment entry and compliance. Some positive treatment produced changes were also noted on the empathy scale. Apart from a motivational intervention, other factors identified by the sample as being influential in the treatment-seeking decision-making process included both internal (e. g., desire for self improvement, acceptance of responsibility for the offending, denial of offending, fear and shame) and external (e. g., awareness of treatment procedures at the Sex Offender Treatment Programme, family support and custody conditions) factors. The discussion focuses on future use of pretherapy, motivational interventions and the integration of such factors.
Keywords: Sex offenders; Rehabilitation; New Zealand; Child molesters